The costs of fatal and non‐fatal falls among older adults - Stevens, J A (BMJ Group, 2006)
OBJECTIVE: To estimate the incidence and direct medical costs for fatal and non‐fatal fall injuries among US adults aged ⩾65 years in 2000, for three treatment settings stratified by age, sex, body region, and type of injury. METHODS: Incidence data came from the 2000 National Vital Statistics System, 2001 National Electronic Injury Surveillance System‐All Injury Program, 2000 Health Care Utilization Program National Inpatient Sample, and 1999 Medical Expenditure Panel Survey. Costs for fatal falls came from Incidence and economic burden of injuries in the United States; costs for non‐fatal falls were based on claims from the 1998 and 1999 Medicare fee‐for‐service 5% Standard Analytical Files. A case crossover approach was used to compare the monthly costs before and after the fall. RESULTS: In 2000, there were almost 10 300 fatal and 2.6 million medically treated non‐fatal fall related injuries. Direct medical costs totaled $0.2 billion dollars for fatal and $19 billion dollars for non‐fatal injuries. Of the non‐fatal injury costs, 63% ($12 billion) were for hospitalizations, 21% ($4 billion) were for emergency department visits, and 16% ($3 billion) were for treatment in outpatient settings. Medical expenditures for women, who comprised 58% of the older adult population, were 2–3 times higher than for men for all medical treatment settings. Fractures accounted for just 35% of non‐fatal injuries but 61% of costs. CONCLUSIONS: Fall related injuries among older adults, especially among older women, are associated with substantial economic costs. Implementing effective intervention strategies could appreciably decrease the incidence and healthcare costs of these injuries.